Conceptual approaches to the formation of regional economic clusters - N. V. Rakuta; T. E. Sitokhova (Управление)
Clustering of the economy of individual territories determines the most effective integration their into the world economic system, makes it possible for the accumulation and optimal use of resources from the point of view of global trends, contributes to the efficiency of state industrial policy. Clusters have become one of the main driving forces and determinants of regional competitiveness, the effectiveness of which is confirmed by world experience. They make it possible to increase the competitiveness not only of their enterprises, but also of specific industries within the region, as well as to expand the introduction of innovations, reduce transaction costs, develop and strengthen the relationship between business, science and the state. The resulting synergistic effect of creating a cluster is not only to increase the efficiency of its work as a whole in comparison with the efficiency of individual participants, but also to mutually strengthen the competitive position of both industry production and its home territory.The content characteristic of the concept of “economic cluster of the region”, which distinguishes the author’s approach from other well-known scientific approaches by the fact that as part of regional clusters, a special kind of them can be distinguished-an economic cluster of small enterprises, which is a localized and geographically concentrated group of small businesses, interconnected and complementary to each other, has been clarified in the article. In the center of cluster education are one or more large and stable in their development enterprises, that provide effective demand, have common (similar) economic interests, a common development strategy aimed at activating the activities of small enterprises in the region.Small enterprises, that are part of the regional economic cluster can provide the region with a higher level of production efficiency and competitiveness in comparison with other non-systemically organized economic structures.